2018
DOI: 10.1002/slct.201702718
|View full text |Cite
|
Sign up to set email alerts
|

InCl3‐Assisted Eco‐Friendly Approach for N‐Fused 1,4‐Dihydropyridine Scaffolds via Ring Opening Michael Addition of Cyclic Nitroketene and Iminocoumarin: Synthesis and DFT Studies

Abstract: A novel strategy was developed for the synthesis of five different N-fused 1,4-dihydropyridine (1,4 DHP) scaffolds such as imidazopyridine, pyridopyrimidine, benzoimidazopyridine, thiazolopyridine and benzopyridooxazine derivatives by coupling nitroketene S,S-acetal, various nitrogen containing dinucleophiles, malanonitrile and substituted salicylaldehydes/aldehydes in the presence of InCl 3 as catalyst in water-EtOH solvent mixture under reflux condition. Furthermore, mechanism for the formation of 1,4-DHPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Further, the synthesized pyrrole derivatives were successfully transformed into biologically significant 6-azaindole derivatives in an efficient manner. In this work, our aim is to develop a new synthetic methodology and explore the chemistry of α-azido ketones for synthesizing novel heterocyclic systems through domino one-pot reactions in a simple synthetic approach.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the synthesized pyrrole derivatives were successfully transformed into biologically significant 6-azaindole derivatives in an efficient manner. In this work, our aim is to develop a new synthetic methodology and explore the chemistry of α-azido ketones for synthesizing novel heterocyclic systems through domino one-pot reactions in a simple synthetic approach.…”
Section: Resultsmentioning
confidence: 99%
“…But due to drawbacks such as harsh reaction conditions, long reaction time, and generally low yield of products, new modifications were made to it to obtain the targeted compounds,1,4-DHPs, in good to excellent yields [ 15 ]. It has been reported that in multicomponent reactions (MCRs), a wide variety of catalysts has been studied for the production of 1,4-DHP derivatives, encompassing various Lewis or Bronsted acids such as Y(OTf) 3 [ 16 ], free nano-Fe 2 O 3 [ 17 ], TMU-33 [ 18 ], InCl 3 [ 19 ]; heterogeneous catalyst such as HClO 4 –SiO 2 [ 20 ], PdRuNi@GO NPs [ 7 ], zeolite [ 21 ], IRMOF-3 [ 22 ]; organ catalyst, CAN [ 23 ], Montmorillonite K10 clay [ 24 ], HClO 4 -SiO 2 [ 25 ], tetrabutylammonium hydrogen sulfate, sodium- and Cs-Norit carbons, fermenting Baker’s yeast [ 26 ], metal triflates with the incorporation of numerous methodologies such as stirring [ 2 ], conventional heating [ 27 ], refluxing [ 22 ], microwave [ 1 ], visible light [ 4 ], and ultrasound irradiations [ 21 ]. Researchers are now focusing on the green aspects of this reaction leading to the usage of various green solvents such as glycerol [ 18 ], water [ 19 ], and ionic liquids [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The numerous attractive features of enamines or dienamines derived from the 1,1-bis(methylthio)-2-nitroethene have made them important intermediates for the construction of a wide variety of S-and N-heterocyclic systems. [27][28][29][30][31][32][33] Hence during recent years, they have been used for the synthesis of various fused heterocycles and drug-like compounds. For examples in 2013 Bazgir et al described a one-pot, four-component synthesis of a novel class of functionalized imidazo[1,2-a]pyridine derivatives starting from readily available inputs including diverse diamines, 1,1-bis(methylthio)-2-nitroethene, aldehydes and activated methylene compounds in EtOH under reux conditions (Scheme 1, Entry a).…”
Section: Introductionmentioning
confidence: 99%